Guillaume de Machaut, The Complete Poetry and Music, Volume 9 : The Motets - Guillaume, de Machaut, approximately 1300-1377 (Book collections on Project MUSE., 2018)
This volume contains the complete 23 polyphonic motets by Machaut. Six of the works are in Latin, and were apparently composed for ceremonial functions. The rest are in French, and are dedicated to subjects of courtly love.